SARS-CoV-2 concentrations and virus-laden aerosol size distributions in outdoor air in north and south of Italy. (January 2021) - Chirizzi, D.; Conte, M.; Feltracco, M.; Dinoi, A.; Gregoris, E.; Barbaro, E.; La Bella, G.; Ciccarese, G.; La Salandra, G.; Gambaro, A.; Contini, D.
Graphical abstract: Highlights: SARS-CoV-2 concentration in outdoor air was measured in north and south Italy. Size distributions of virus-laden aerosol were investigated at both sites. SARS-CoV-2 concentrations were <0.8 copies m −3 for each size range. Outdoor airborne transmission does not explain differences in COVID-19 outbreaks. Outdoor air was not infectious and safe for the public excluding crowded sites. Abstract: The COVID-19 disease spread at different rates in the different countries and in different regions of the same country, as happened in Italy. Transmission by contact or at close range due to large respiratory droplets is widely accepted, however, the role of airborne transmission due to small respiratory droplets emitted by infected individuals (also asymptomatic) is controversial. It was suggested that outdoor airborne transmission could play a role in determining the differences observed in the spread rate. Concentrations of virus-laden aerosol are still poorly known and contrasting results are reported, especially for outdoor environments. Here we investigated outdoor concentrations and size distributions of virus-laden aerosol simultaneously collected during the pandemic, in May 2020, in northern (Veneto) and southern (Apulia) regions of Italy. The two regions exhibited significantly different prevalence of COVID-19. Genetic material of SARS-CoV-2 (RNA) was determined, using both real time RT-PCR and ddPCR, in air samples collected using PM10 samplers and cascade impactors able to separate 12 size ranges from nanoparticles (diameter D < 0.056 µm) up to coarse particles (D > 18 µm). Air samples tested negative for the presence of SARS-CoV-2 at both sites, viral particles concentrations were <0.8 copies m −3 in PM10 and <0.4 copies m −3 in each size range investigated. Outdoor air in residential and urban areas was generally not infectious and safe for the public in both northern and southern Italy, with the possible exclusion of very crowded sites. Therefore, it is likely that outdoor airborne transmission does not explain the difference in the spread of COVID-19 observed in the two Italian regions.